Edukasi Konten Digital terhadap Anak Usia Dini di TK Negeri 3 Suryoputran Kota Yogyakarta - Dyaloka Puspita Ningrum (Universitas Muhammadiyah Semarang, 2023)
According to the Hootsuite We Are Social report, internet use in Indonesia continues to increase and is higher than the total population. Pierre Levy's perspective with two approaches, namely: social interaction and social integration is also able to show changes in behavior as well as shifts in public activity as a form of adaptation in the current era of disruption. The existence of the internet is like a double-edged sword, especially for groups of children at an early age who are very vulnerable to being exposed to negatively charged information and content, even though this condition has also been regulated in the Information and Electronic Transactions Law / UU ITE. This Community Service Activity is located at TK Negeri 3 Suryoputran Yogyakarta City